Three-body collapse for Tabakin potentials and the Thomas effect - Delfino, A.; Adhikari, Sadhan K. [UNESP]; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 1992)
A system constituted of three bosons interacting via two-body separable potentials with fixed two-boson binding is known to lead to bound-state collapse in the case where the potential parameters allow two-boson S-matrix poles close to (resonance) and on (continuum bound state) the real momentum axis. The collapse is shown to be accompanied by an increase in the average kinetic energy of the two-body bound state, which signals a decrease in the range of the two-body interaction for fixed two-body binding. The collapse is claimed to be a manifestation of the well-known Thomas effect which leads to a collapse of the three-body system when the range of the two-body interaction goes to zero for a fixed two-body binding. © 1992 The American Physical Society.